Information Technology-Based Law Enforcement in Increasing Public Trust in the Police - Resa F Marasambessy (Gema Wiralodra, 2023)
The present article offers a succinct summary of the scholarly investigations on the function of information technology (IT) in law enforcement and its influence on the level of trust that the public places in this institution. This study aims to investigate the significance of information technology (IT) in law enforcement and its correlation with the level of public confidence in law enforcement agencies. The methodology employed in this study is a literature review, which involves a systematic analysis of pertinent research articles and scholarly papers to extract significant insights. The results underscore the multifaceted uses of information technology in law enforcement, encompassing data mining and crime investigation systems, sophisticated IT methodologies, and knowledge representation and advisory systems. The utilization of IT applications has been observed to augment law enforcement capabilities and promote the establishment of public trust in the police. The study's findings suggest that the appropriate and principled utilization of information technology can facilitate openness, liability, and civic participation, resulting in enhanced rapport between law enforcement entities and the populace. The present study offers significant contributions to law enforcement, policymaking, and research by providing insights on how information technology (IT) can improve public trust in the police.